(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The proliferation of internet users around the globe, including in India, is hastening profoundchanges in the marketing landscape. According to customer preferences, Emerging channels, dataproliferation, and other factors, it is now crucial for marketers to make the most of constantly developingdigital marketing tactics. In India, digital marketing has replaced traditional methods as the goldstandard, opening up new expansion opportunities. Unlike conventional marketing, digital marketingoffers a real-time scenario of marketing communication and includes the use of channels andtechnologies that allow a company to analyze marketing campaigns and boost accuracy. Marketinguses one or more forms of media advertising, such as social media, the internet, digital, television,radio, and mobile phones, to directly promote productservices or brands. The Influences of digitalmarketing on online stores need to be investigated. This research will provide light on the state of digitaladvertising as a whole. Examining the global influences of modern business competitiveness and how ithas altered age-old marketing strategies.